Pengelolaan Keuangan Pemerintah di Masa Pandemi Covid 19 (Kasus Pada Pemerintah Provinsi Riau) - Basri, Yesi Mutia; Gusnardi, Gusnardi (Jati: Jurnal Akuntansi Terapan Indonesia, 2021)
This study aims to observe how local government financial management is in the face of the Covid-19 Pandemic—in particular, observing how budgeting, administration, and accountability of the Riau Provincial Government regarding the Covid-19 Pandemic. The research method used is a qualitative method with a type of case study. The data collection techniques used in-depth interviews, observation, and documentation. To ensure the validity of the data, triangulation was carried out by carrying out source triangulation and technical triangulation. The informants in this study consisted of key informants, primary informants, and supporting informants. Key informants are the head of the budget, the head of the treasury, and the head of the accounting and reporting sub-section. While the primary informants and supporting informants were selected using the snowball sampling technique. Data analysis was carried out by collecting data, reducing data display data, and making conclusions. The results of the analysis show that the impact of the Covid-19 Pandemic caused the Riau Provincial Government to refocus and reallocate the budget four times. At the administrative and accountability stages, there are problems with recording Unexpected Expenditures, namely the absence of technical guidelines regarding the administration of Unexpected Expenditures, determining spending limits for emergencies and urgency. Another problem is the absence of valid data for the distribution of aid funds for MSMEs affected by Covid-19 as well as valid documents in the recording of grant assistance from third parties. This research contributes to the government in making policies in financial management in a disaster emergency.Keyword: The Covid-19 Pandemic, Financial Management, Refocusing, Reallocation, Administration, Accountability AbstrakPenelitian ini bertujuan untuk mengobservasi bagaimana pengelolaan keuangan Pemerintah Daerah dalam menghadapi Pandemi Covid-19 ini. Secara khusus mengobservasi bagaimana penganggaran, penatausahaan dan pertanggungjawan Pemerintah Provinsi Riau terkait Pandemi Covid-19. Metode penelitian yang digunakan adalah metode kualitatif dengan jenis studi kasus. Teknik pengumpulan data menggunakan teknik wawancara medalam, observasi dan dokumentasi. Untuk meyakinkan keabsahan data, triangilasi dilakukan dengan melaksanakan triangulasi sumber dan triangulasi teknik. Informan dalam penelitian ini terdiri dari informan kunci, informan utama dan informan pendukung. Informan kunci adalah Kabid anggaran, kabid perbendaharaan dan kasubid akuntansi dan pelaporan. Sedangkan informan utama dan informan pendukung dipilih dengan teknik snowball sampling. Analisis data dilakukan  dengan tahap pengumpulan data, reduksi data display data dan melakukan membuat kesimpulan. Hasil analisis menunjukkan bahwa Dampak Pandemi Covid-19 menyebabkan Pemerintah Provinsi Riau melakukan refocusing dan realokasi anggaran sebanyak empat kali pergeseran anggaran. Pada tahap penatausahaan dan pertanggungjawaban terdapat permasalahan pencatatan pada Belanja Tidak Terduga yaitu tidak adanya juknis tentang penatausahaan Belanja Tidak Terduga, penentuan batasan belanja untuk keadaan darurat dan mendesak.  Permasalahan lainnya yaitu tidak  adanya data yang valid untuk penyaluran dana  bantuan bagi UMKM yang terdampak Covid-19 serta dokumen yang valid dalam pencatatan bantuan hibah dari pihak ke tiga. Penelitian ini memberikan kontribusi kepada pemerintah dalam membuat kebijakan dalam pengelolaan keuangan pada keadaan darurat bencana. Kata Kunci :  Pandemi Covid-19, Pengelolaan Keungan, Refocusing, Realokasi, Penatausahaan, Pertanggungjawaban